Prevalence and correlates of unhealthy weight control behaviors: findings from the national longitudinal study of adolescent health - Stephen, Eric M (BioMed Central, 2014)
BACKGROUND: A recent study examined the prevalence, clinical correlates, age trends, and stability of unhealthy weight control behaviors (UWCB; purging and diet pill use) in a nationally representative sample of Norwegian boys and girls. The purpose of this study was to provide similar, comparative analyses for a nationally representative sample of American youth. METHODS: Data were extracted from the restricted use data files of survey Waves I, II, and III of the National Longitudinal Study of Adolescent Health (Add Health), selecting all participants who at Wave I had provided information on age, sex, and UWCB. Using UWCB information, three groups were created (purging, diet pill use, and no recent UWCB “controls”) and compared on indicators of adverse health or mental health. RESULTS: Girls consistently were more likely than boys to report UWCB. UWCB were significantly associated with higher body mass index, self-perception of being overweight, low self-esteem, depression, and delinquency. Prevalence estimates for purging remained relatively constant across the three survey waves; in contrast, diet pill use was especially common at Wave III. CONCLUSIONS: Age trends, gender differences, and clinical correlates of change in the likelihood of UWCB between Waves I-III were all identified in analyses comparing purging and diet pill use in American adolescents. Females and older adolescents were specifically more likely to engage in pill use than purging, and individuals with increased weight dissatisfaction, a history of delinquent behaviors, more depression symptoms, or lower self-esteem were more likely to engage in an unhealthy weight control behavior over time. While the Norwegian study found that prevalence of purging was lower among young adult participants, our results suggested that there were no significant differences in prevalence between age groups.